PENGENALAN KOSA KATA BAHASA INGGRIS MELALUI MEDIA AUDIO VISUAL (ANIMASI) PADA PAUD - Noni Marlianingsih (Faktor Jurnal Ilmiah Kependidikan, 2016)
Abstract: The purpose of community service is to provide an introduction to masteryof the English vocabulary through the use of audio-visual media in children aged 4-6 years in the residential district Pandak Graha Bogor years 2014-2015. Extensionmethod this time using audio-visual media such as animated. The results showed thatthe use of public service media in the form of audio-visual media animation canincrease the sense of a great interest in learning and improve the mastery of Englishvocabulary. The steps of the use of audio-visual media in the form of animated are as follows: preparing and testing the media before learning activities; first explain the activities to be carried out together with rules to follow activities; Creating an atmosphere where learning so that children feel happy; turn on the TV and DVD; invites children to see and pay attention to see; invite children to say the word together; assigning children one by one to repeat and imitate the words in audio-visual form of animated.Keywords: English Vocabulary, Media Audio Visual, Early Childhood